Inflaç\~ao, desemprego e choques cambiais: Uma revis\~ao da literatura sobre a curva de Phillips no Brasil - Adolfo Sachsida (Instituto de Pesquisa Econômica Aplicada (IPEA), 2014)
– This article summarizes the studies about the Phillips curve in the Brazilian economy. Overall, the results are very sensitive to the time period, to the proxies adopted, to the econometric approach, and to the frequency and lags allowed to the variables. These results cast some doubts about the ability of the Phillips curve to describe the dynamics of inflation in the Brazilian economy.
Keywords: E31; E24; 330; Phillips curve; inflation; unemployment; exchange rate